Serological survey for seroneutralizing antibodies to Aujeszky disease virus - ΠΑΠΠΟΥΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The results of a serological survey for detecting seroneutralizing antibodies to Aujeszky’s Disease virus are reported. 625 pig sera, mainly from fattening pigs, of 63 herds in 9 départements, are examined. Only 7 sera, belonging to two herds from Attica, were found positive. The serological data in correlation to the few cases of clinical disease diagnosed last year in Greece, show that the infection is for the time being very limited.